RIP1 Perturbation Induces Chondrocyte Necroptosis and Promotes Osteoarthritis Pathogenesis via Targeting BMP7 - Cheng, Jin; Duan, Xiaoning; Fu, Xin; Jiang, Yanfang; Yang, Peng; Cao, Chenxi; Li, Qi; Zhang, Jiying; Hu, Xiaoqing; Zhang, Xin; Ao, Yingfang (Frontiers in Cell and Developmental Biology, 2021)
Osteoarthritis (OA) is a highly prevalent and debilitating joint disorder that characterized by progressive destruction of articular cartilage. There is no effective disease-modifying therapy for the condition due to limited understanding of the molecular mechanisms on cartilage maintenance and destruction. Receptor-interacting protein kinase 1 (RIP1)-mediated necroptosis plays a vital role in various diseases, but the involvement of RIP1 in OA pathogenesis remains largely unknown. Here we show that typical necrotic cell morphology is observed within human OA cartilage samples in situ, and that RIP1 is significantly upregulated in cartilage from both OA patients and experimental OA rat models. Intra-articular RIP1 overexpression is sufficient to induce structural and functional defects of cartilage in rats, highlighting the crucial role of RIP1 during OA onset and progression by mediating chondrocyte necroptosis and disrupting extracellular matrix metabolism homeostasis. Inhibition of RIP1 activity by its inhibitor necrostatin-1 protects the rats from trauma-induced cartilage degradation as well as limb pain. More importantly, we identify bone morphogenetic protein 7 (BMP-7) as a novel downstream target that mediates RIP1-induced chondrocyte necroptosis and OA manifestations, thereby representing a non-canonical regulation mode of necroptosis. Our study supports a model whereby the activation of RIP1-BMP7 functional axis promotes chondrocyte necroptosis and subsequent OA pathogenesis, thus providing a new therapeutic target for OA.